2019
DOI: 10.1016/j.jpag.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical Outcomes in Adult Patients Born with Complex Anorectal Malformations and Cloacal Anomalies: A Literature Review

Abstract: a b s t r a c tPatients born with complex anorectal malformations often have associated M€ ullerian anomalies, which might affect fertility and obstetrical outcomes. Other vertebral-anorectal-tracheoesophageal-renal-limb associations, such as renal or cardiac anomalies, could also affect pregnancy intention, fertility rates, and recommendations about mode of delivery or obstetrical outcomes. Associated conditions present at birth, like hydrocolpos, could also potentially affect fertility. Depending on the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…More than half of patients born with a cloacal malformation have an associated Müllerian anomaly, most commonly uterine didelphys, but other anomalies including unicornuate uterus and uterine agenesis have been reported as well [4,8]. We reviewed different Müllerian anomalies such as number of cervices, presence of vaginal septum, uterine malformations and somewhat surprisingly did not find any significance in these variables to predict the need of vaginal replacement in our population.…”
Section: Discussionmentioning
confidence: 76%
“…More than half of patients born with a cloacal malformation have an associated Müllerian anomaly, most commonly uterine didelphys, but other anomalies including unicornuate uterus and uterine agenesis have been reported as well [4,8]. We reviewed different Müllerian anomalies such as number of cervices, presence of vaginal septum, uterine malformations and somewhat surprisingly did not find any significance in these variables to predict the need of vaginal replacement in our population.…”
Section: Discussionmentioning
confidence: 76%
“…Other congenital abnormalities commonly associated with MDAs include vertebral body anomalies (29%) (that is, fused or wedged vertebral bodies, spina bifida; 22–23%), heart abnormalities (14.5%), and syndromes such as the Klippel-Feil syndrome (7%) [ 6 ]. Other conditions involving vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities (VACTERL association), such as renal or cardiac anomalies in patients with MDAs, could also affect their conception, fertility, modes of delivery, and obstetrical outcomes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 A recent review article reported on all available obstetrical outcomes in the literature in patients with CM. 58 There were no maternal mortalities and the most common complications were recurrent urinary tract infections and premature deliveries secondary to spontaneous preterm labor. Patients with CM had varying modes of delivery including vaginal delivery, operative vaginal delivery, and cesarean section.…”
Section: Gynecological and Sexual Functionmentioning
confidence: 92%